Why Enroll in a Graduate-level Vocational Education Program?: Exploring Views of Graduate Students Using Latent Dirichlet Allocation Topic Modelling - Tejero, Ma Zosima Labro (FKIP Universitas Lampung, 2023)
Objectives: The main objective of this study was to identify the most frequent words, the sentiment, and the underlying themes in the students' responses regarding their enrollment in a graduate-level vocational education program. Methods: Word Cloud generation, VADER Sentiment Analysis and Latent Dirichlet Topic modelling were utilized to analyze the collected data. Findings: The most frequent words in the responses of students were